2017
DOI: 10.1371/journal.pone.0189128
|View full text |Cite
|
Sign up to set email alerts
|

Occult RV systolic dysfunction detected by CMR derived RV circumferential strain in patients with pectus excavatum

Abstract: AimsTo investigate the right ventricular (RV) strain in pectus excavatum (PE) patients using cardiac magnetic resonance tissue tracking (CMR TT).Materials and methodsFifty consecutive pectus excavatum patients, 10 to 32 years of age (mean age 15 ± 4 years), underwent routine cardiac magnetic resonance imaging (CMR) including standard measures of chest geometry and cardiac size and function. The control group consisted of 20 healthy patients with a mean age of 17 ± 5 years. RV longitudinal and circumferential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
(33 reference statements)
2
23
0
1
Order By: Relevance
“…A higher myocardial strain in the mid and apical portions of the ventricles has been interpreted as a possible compensation mechanism to enhance ventricular output against basal sternal compression. 20,21 Alternatively, myocardial strain impairment in PE subjects might reflect intraventricular dyssynchrony due to compressive phenomena within chest rather than a subclinical myocardial dysfunction. The blue zones that we observed in our patient at basal and mid-level in both 2D-STE derived bull's eye plots images suggested segmental paradoxical systolic expansion.…”
Section: Discussionmentioning
confidence: 99%
“…A higher myocardial strain in the mid and apical portions of the ventricles has been interpreted as a possible compensation mechanism to enhance ventricular output against basal sternal compression. 20,21 Alternatively, myocardial strain impairment in PE subjects might reflect intraventricular dyssynchrony due to compressive phenomena within chest rather than a subclinical myocardial dysfunction. The blue zones that we observed in our patient at basal and mid-level in both 2D-STE derived bull's eye plots images suggested segmental paradoxical systolic expansion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a disadvantage is that UCG is easily influenced by RV structure, retrosternal position, and motion complexity. 32 In 2016, Maagaard and Heiberg 33 searched three databases from 1972 to 2016 and 21 published studies that contained complete data were included, in which UCG data were compared before and after PE procedure to investigate cardiac function during rest and exercise. Among these included studies, Chao et al 34 and Sigalet et al 35 showed an increase in postoperative right ventricular output.…”
Section: Echocardiographymentioning
confidence: 99%
“…Вплив операції малоінвазивної корекції ЛДГК за Nuss на гемодинамічні показники та кардіальну функцію досить жваво обговорюється в літературі, хоч на сьогодні немає єдиного бачення даної проблеми. Деякі автори доводять позитивний вплив такої корекції на серцевий викид та ударний об'єм серця, тоді як інші заперечують такий ефект [5,9,10,14]. Ця проблема набуває актуальності ще і через те, що при відсутності покращення кардіореспіраторної функції внаслідок корекції ЛДГК операція вважається суто косметичною, та страхові компанії не компенсують її вартість пацієнтам [15].…”
Section: обговоренняunclassified